Performance and health in combined events: A scoping review - Edouard, P. (Scandinavian Journal of Medicine & Science in Sports, 2026)
Combined events are an Athletics discipline with specific and particular challenges for performance and health, supporting the interest of focused research on this discipline, despite concerning a small proportion of athletes. The study aim was to summarize and map the available scientific literature on performance and health of combined events to establish the current level of understanding and identify knowledge gaps that require further investigation. A scoping review was conducted searching peer-reviewed articles dealing with performance and/or health in combined events (i.e., pentathlon, heptathlon or decathlon) on the MEDLINE (via PubMed), EMBASE (via Ovid), Web of Science, and Google Scholar databases, from inception to October 13, 2025. In total, 111 articles were included, with 95.5% as primary research, 95.5% using quantitative approach, 22.5% with a level of evidence 1b and 48.6% 2b, and 56.8% with study aim(s) focused on combined events understanding and/or analyzing. 64.0% articles dealt with performance and 59.5% with health, including 23.4% dealing with both. Regarding performance, the majority of articles dealt with performance analysis/tactics/data management (56.3%), followed by physiology (21.1%), and nutrition (11.3%). Regarding health, the majority of articles dealt with injuries (62.1%), followed by physiology (22.7%), illnesses (18.2%), and nutrition (12.1%). These findings (i) can help to suggest some clinical implications for performance enhancement and health protection, and (ii) highlighted the need for continuing research on performance and/or health in combined events, preferably with prospective design, large athletes' sample sizes, focused on underrepresented populations (e.g., women, adolescents, Masters athletes), over one or more Athletics season.